Changes in left ventricular repolarization and ion channel currents following a transient rate increase superimposed on bradycardia in anesthetized dogs. - Rubart M; Lopshire JC; Fineberg NS; Zipes DP (Journal of Cardiovascular Electrophysiology, 2000)
Introduction: We previously demonstrated in dogs that a transient rate increase superimposed on bradycardia causes prolongation of ventricular refractoriness that persists for hours after resumption of bradycardia. In this study, we examined changes in membrane currents that are associated with this phenomenon. Methods and Results: The whole cell, patch clamp technique was used to record transmembrane voltages and currents, respectively, in single mid-myocardial left ventricular myocytes from dogs with 1 week of complete AV block; dogs either underwent 1 hour of left ventricular pacing at 120 beats/min or did not undergo pacing. Pacing significantly heightened mean phase 1 and peak plateau amplitudes by ~6 and ~3 mV, respectively (P < 0.02), and prolonged action potential duration at 90% repolarization from 235 ± 8 msec to 278 ± 8 msec (1 Hz; P = 0.02). Rapid pacing-induced changes in transmembrane ionic currents included (1) a more pronounced cumulative inactivation of the 4-aminopyridine-sensitive transient outward K+ current, Ito, over the range of physiologic frequencies, resulting from a ~30% decrease in the population of quickly reactivating channels; (2) increases in peak density of L-type Ca2+ currents, ICaL, by 15% to 35% between +10 and +60 mV; and (3) Increases in peak density of the Ca2+-activated chloride current, ICl.Ca, by 30% to 120% between +30 and +50 mV. Conclusion: Frequency-dependent reduction in Ito combined with enhanced ICaL causes an increase in net inward current that may be responsible for the observed changes in ventricular repolarization. This augmentation of net cation influx is partially antagonized by an increase in outward ICaCl.